Apical Sealing Ability of Different Endodontic Sealers Using Glucose Penetration Test: A Standardized Methodological Approach - Nik Rozainah Nik Abdul Ghani; Tahir Yusuf Noorani; Aimi Kamarudin; Galvin Sim Siang Lin (Cumhuriyet Dental Journal, 2020)
Objectives: To compare the apical sealing ability of four endodontic sealers based on glucose penetration method and validate the uses of contralateral teeth to provide a well-balanced experimental group.